▼Interferon beta-1b - hope or hype?. Issue 2 (February 1996) - Unknown
Abstract : In November 1995, the European Commission gave approval for interferon beta-1b (Betaferon - Schering) to be marketed throughout the European Union "for the reduction of frequency and degree of severity of clinical relapses in ambulatory patients with relapsing/remitting multiple sclerosis". The drug was launched in the UK in December, with the manufacturer claiming it to be "a significant step forward in the treatment of multiple sclerosis". We review the clinical data on the effectiveness of interferon beta-1b and assess its place in the management of multiple sclerosis.